Development of Dila Bisa Media Based on Lectora Inspire in Arabic Language Learning - Majda Qudsiyatul Malikh; Ahmad Mubaligh; Alvira Nirma Wijayanti (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
This research aimed to develop and measure the effectiveness of the